Time elapsed since peruvian children's last dental care and head of household educational attainment: findings from a national database - María Claudia Garcés-Elías; César Eduardo Del Castillo-López; Jorge A. Beltrán; Roberto A. León-Manco (BMC, 2023)
Abstract Background It has been documented that the parents' highest level of education has an impact on their children's access to oral health services and the frequency of their use.This study aimed to determine the association between time elapsed since peruvian children's last dental care and head of household educational attainment. Methods Cross-sectional study using a database of children aged 0 to 11 years, with a final sample of 8012 participants. The dependent variable in this study was the time elapsed since last dental care and the independent variable was the head of household educational attainment. Other covariates considered were natural region, area of residence, place of residence, altitude, wealth index, health insurance coverage, sex and age. Descriptive, bivariate and multivariate statistical analyses were applied. Results Time elapsed since last dental care in the year 2021 was 5.68 years (SD = 5.25). A hierarchical multiple linear regression analysis was performed, analyzing the variables dimensions by separate and joint models. When head of household educational attainment was analyzed, there was no statistical significance (p = 0.262); however, other models did (p < 0.05). Model 4, which addresses all dimensions, was significant (p < 0.001) with an R2% of 0.011 and constant equal to 5.788; it showed significance with place of dental care, health insurance, altitude and age. Conclusions No association was found between head of household educational attainment and time elapsed since last dental care; however, the latter was associated with place of care, health insurance coverage, altitude and age in Peruvian children.